Giant Arachnoid Granulations Mimicking Pathology: A Report of Three Cases. Issue 3 (June 2014) - De Keyzer, Bart; Bamps, Sven; Van Calenbergh, Frank; Demaerel, Philippe; Wilms, Guido
We describe three cases of incidentally found lesions in the dural venous sinuses on magnetic resonance imaging, that other had erroneously considered pathological entities. We made the diagnosis of giant arachnoid granulations. The differential diagnosis with thrombosis or intrasinusal tumoral lesions was easily made on the basis of three typical radiological features of the granulations: the hyperintensity of the lesions on FLAIR, a blood vessel within the lesion and bone erosion.